Voucher Diskon, Online Customer Review Berpengaruh terhadap Minat Beli Ulang: (GoFood di Surakarta) - Eka Darma Ningtyas; Indra Hastuti; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of discount vouchers on repurchase interest in partial terms, to determine the influence of online customer reviews on repurchase interest, and to determine the influence of discount vouchers and online customer reviews on repurchase interest in a case study at GoFood in Surakarta simultaneously. The sample was 100 respondents using a sampling technique using purposive sampling. This research used quantitative methods with SPSS 25 64 bit data analysis tools. Data analysis techniques in this research use validity tests, reliability tests, classical assumption tests, T tests, and F tests. The results of this study show that there is a positive and significant influence of discount vouchers on repurchase interest, there is a positive and significant influence of online customer reviews on interested in buying again. Then the research results concluded that simultaneously there was a positive